Improved Growth Velocity Using a New Liquid Human Milk Fortifier in Very Low Birth Weight Infants: A Multicenter, Retrospective Study - Moya, Fernando; Fowler, Jennifer; Florens, Adrian; Dombrowski, Jennifer; Davis, Olivia; Blanks, Tiffony; Gratton, Austin (American Journal of Perinatology, 2025)
This study aimed to compare growth outcomes and tolerance among very low birth weight (VLBW) infants receiving a new, liquid human milk fortifier (LHMF-NEW) or a human milk fortifier-acidified liquid (HMF-AL).Retrospective, multicenter study of 515 VLBW infants in three regional neonatal intensive care units. The primary objective was to compare growth velocity (g/kg/d) during fortification between groups by repeated measures regression. Secondary outcomes of interest were feeding tolerance and the incidence of late-onset sepsis, necrotizing enterocolitis, and metabolic acidosis. Student's t, analysis of variance, Wilcoxon, and Kruskal–Wallis tests were used for numeric variables, or chi-squared and Fisher's exact test for categorical variables.No demographic differences were identified between the groups (HMF-AL, n = 242; LHMF-NEW, n = 273). Growth velocity during fortification was significantly higher in the group receiving LHMF-NEW, despite relatively similar total fluid, calorie, or protein intake (p = 0.001). Feeding intolerance was comparable between fortifiers. Necrotizing enterocolitis and late-onset sepsis did not differ between groups and metabolic acidosis was diagnosed less frequently with the LHMF-NEW. Anthropometric measures at discharge and length of stay were comparable.Infants receiving human milk fortified with the LHMF-NEW had faster growth velocity during fortification, similar tolerance, and less metabolic acidosis compared with an earlier cohort of infants who received human milk fortified with an HMF-AL.
Keywords: human milk fortification; human milk; growth velocity; postnatal nutrition; very low birth weight infants